2023
DOI: 10.5114/pjr.2023.130977
|View full text |Cite
|
Sign up to set email alerts
|

Children with back pain – a radiologist’s approach

Hanna Potoczna,
Jan Bereda,
Anna Mania
et al.

Abstract: IntroductionThe aim of the study was to analyse magnetic resonance imaging (MRI) of paediatric patients referred because of back pain.Material and methodsThe retrospective analysis included the medical records of 328 patients referred in 2020-2022 to the Department of Paediatric Radiology for spine examination. The criterion for inclusion in the analysed group was back pain as the dominant symptom. This symptom occurred in 20% (68 patients) of referrals for MRI examinations. The examination was performed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to present a panoramic view of the clinical characteristics (obtained after a comprehensive clinical examination summarized in the medical record) and presumed etiologies (after spine imaging) of JOBP in children and adolescents in an African setting. Although not exhaustive, the imaging findings observed in this study are broadly in line with the data available, ranging from “evil” etiologies such as spondylodiscitis or neoplasia to “non-specific” etiologies ( 3 , 4 , 7 , 24 , 25 ). Despite this significant strength of our study, there are several limitations.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study to present a panoramic view of the clinical characteristics (obtained after a comprehensive clinical examination summarized in the medical record) and presumed etiologies (after spine imaging) of JOBP in children and adolescents in an African setting. Although not exhaustive, the imaging findings observed in this study are broadly in line with the data available, ranging from “evil” etiologies such as spondylodiscitis or neoplasia to “non-specific” etiologies ( 3 , 4 , 7 , 24 , 25 ). Despite this significant strength of our study, there are several limitations.…”
Section: Discussionsupporting
confidence: 85%
“…In fact, in a recent study aimed at determining the natural history of disc changes from childhood to early adulthood and the possible association of these changes with low back pain, the authors showed that changes in the intervertebral disc signal on MRI were not associated with the presence of low back pain in childhood, adolescence and adulthood ( 26 ). However, MRI is increasingly used as a first-line imaging modality when at least one red flag is present and severe pathology is suspected in a child with back pain ( 11 , 25 ). There is also an ambiguous relationship between scoliosis and back pain.…”
Section: Discussionmentioning
confidence: 99%